European survey of newborn bloodspot screening for CF: opportunity to address challenges and improve performance - KARADAĞ, BÜLENT TANER (My University, 2023)
Background: The aim of this study was to record the current status of newborn bloodspot screening (NBS) for CF across Europe and assess performance. Methods: Survey of representatives of NBS for CF programmes across Europe. Performance was assessed through a framework developed in a previous exercise. Results: In 2022, we identified 22 national and 34 regional programmes in Europe. Barriers to establishing NBS included cost and political inertia. Performance was assessed from 2019 data reported by 21 national and 21 regional programmes. All programmes employed different protocols, with IRT-DNA the most common strategy. Six national and 11 regional programmes did not use DNA analysis. Conclusions: Integrating DNA analysis into the NBS protocol improves PPV, but at the expense of increased carrier and CFSPID recognition. Some programmes employ strategies to mitigate these outcomes. Programmes should constantly strive to improve performance but large datasets are needed to assess outcomes reliably.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Chest Diseases and Allergy; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SOLUNUM SİSTEMİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; RESPIRATORY SYSTEM; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Akciğer ve Solunum Tıbbı; Pediatrics, Perinatology and Child Health; Pulmonary and Respiratory Medicine; CFSPID, carriers; CFTR gene analysis; Cystic fibrosis; IRT; Newborn bloodspot screening; PAP